Evaluation of New Zealand’s Trade and Direct Investment Intensities with Major Trading Partners (Asian Business Research, 2017)
New Zealand (NZ) has been implementing liberal economic policies since 1980s. Accordingly, NZ has negotiated Free Trade Agreements with several countries. NZ is also the founding member of the Asia Pacific Economic Co-operation (APEC) which aims to achieve sustainable economic growth and prosperity among the countries in the Asia-Pacific Region, through free trade, investment and rapid regional economic integration. The bilateral FTAs include the Closer Economic Relations Agreement (CER) with Australia in 1983, Singapore (2001), and China (2008), Malaysia (2010), Hong Kong, China (2011) which are also member economies of the APEC. The consequence is an increase in trade as well as investment flows from Australia, Japan, Singapore, USA, and China. Presently, Australia is the largest export destination for New Zealand accounting for about 20% of merchandise exports, and a similar percent of merchandise imports. Australia is also the largest investor in NZ accounting for 56% of FDI in New Zealand. Singapore is NZ’s 6th largest trading partner and China is the second largest trading partner. Singapore, and Hong Kong, China each account for 4.5% of NZ’s FDI stock. The aim of this paper is to investigate the changing pattern of NZ’s total trade with these countries and inward FDI stock from these countries. The methodology consists of calculating and interpreting the Trade Intensity Indices and FDI Intensity Indices to gauge the significance of these two ratios at bilateral and regional level.